Dimethyl disulfide (DMDS) as an effective soil fumigant against nematodes in China - Yan, Dongdong; Cao, Aocheng; Wang, Qiuxia; Li, Yuan; Canbin, Ouyang; Guo, Meixia; Guo, Xiaoqin (PloS one, 2019)
Root-knot nematode is an important soil pest in horticulture crops and constrains the protected cultivation development after methyl bromide (MB) was phased out in China. Dimethyl disulfide (DMDS) exhibits excellent efficacy against nematodes. Laboratory experiments and field trials were set up to clarify DMDS dose, efficacy, and yield. A dose-response experiment using three methods showed that DMDS presented high efficacy against the nematode Meloidogyne incongnita. The LC50 values of direct fumigation activity in the dessicator method were 0.086 and 0.070 mg L-1 for DMDS and 1,3-D, 29.865 and 18.851 mg L-1 for DMDS and 1,3-D of direct contact activity in the small tube method, 6.438 and 3.061 mg L-1 for DMDS and 1,3-D of soil fumigation activity in the soil fumigation method, respectively. The field trials indicated that DMDS showed an excellent efficacy of 80%-94% on root-knot nematode applied at 10-100 g m-2 on tomato in Tongzhou, Beijing. The crop yields showed no significant difference after applying 10-80 g m-2 DMDS. Results indicate that DMDS applied at 10 g m-2 for controlling root-knot nematode in Beijing is cost effective. In conclusion, DMDS is an excellent soil fumigant that can be used for controlling root-knot nematode and can be an potential novel alternative to MB in China.